3D visual inspection system framework for structural condition monitoring and analysis - Insa-Iglesias, Maria; Jenkins, Mark David; Morison, Gordon (Automation in construction, 2021)
Despite the increase in algorithmic solutions to enhance manual, time-consuming and inaccurate Structural Condition Monitoring assessment, this field currently lacks an effective framework of presenting the output of these algorithms in an understandable and repeatable manner to structural examiners. To solve this issue, a 2D/3D Visual Inspection framework is proposed to allow the creation of a system that detects, visualizes and evaluates structural defects. The resulting system allows structural examiners to conduct a thorough, intelligent structural condition monitoring assessment, who wish to utilize AI technology. This system consists of the Visual Analytics Interface and the 3D Virtual Inspector. The Visual Analytics Interface is an interactive dashboard formed by the following components: the Map, the Graph and the Panel. The 3D Virtual Inspector allowing examiners the exploration of the structural defects with superimposed augmented visualization onto the 3D structure reconstruction. This work presents a case study focused on structural examination of tunnels to demonstrate the applicability of the proposed system. [Display omitted] •A 2D/3D Visual Inspection System framework is introduced.•The system framework stages are data collection, data processing and interface development.•The system consists of a dashboard, a 3D reconstruction and superimposed augmented visualizations.•This framework facilitates fast and repeatable expert visual structural inspections.•Examiners evaluate structural defects using a photorealistic virtual environment.